Californication The fifth season - Duchovny, David; Adlon, Pamela, 1966-; Martin, Madeleine, 1993-; McElhone, Natascha, 1971-; Handler, Evan; Showtime Entertainment (Madrid : Paramount Home Entertainment, 2012)
Author Hank Moody's life is spinning out of control as he juggles his sex and drug addictions while raising a daughter and trying to win back the love of his life.
JFK to LAX -- Way of the fist -- Boys & girls -- Waiting for the miracle -- Ride along -- Love song -- Here I go again -- Raw -- At the movies -- Perverts & whores -- Party -- Hell ain't a bad place to be.
Special features.
Creator, Tom Hapinos ; co-executive producers, Lou Fusaro, Melanie Greene ; executive producers, Tom Kapinos, David Duchovny.
David Duchovny, Natascha McElhone, Pamela Adlon, Madeleine Martin, Evan Handler.
ICCA rating: 12 years or more.
DVD, region 2, widescreen (1.78.1); Dolby Digital 5.1 surround or 2.0 stereo.
English dubbed French or Italian dialogue with optional English, Spanish, French, German, Italian and Dutch subtitles.
Keywords: Television comedies